ARTIFICIAL INTELLIGENCE IN TOURISM & HOSPITALITY – THE PERCEPTION OF TOURISTS AND TOURISM COMPANIES IN ROMANIA - TUTUNEA, Mihaela-Filofteia (Studia Universitatis Babeș-Bolyai Negotia, 2021)
In a world where everyday life is directly influenced and focused on the use of technology as a support for individual and professional daily activity, we are all witnessing an increasingly obvious change in human interaction; we all notice how interpersonal interaction is rapidly being replaced by new technologies, solutions and application such as IoT and AI and which are going to completely change the perspective on human life so far. From this perspective and in the conditions of the ongoing pandemic, the present study focused on identifying the changes brought by AI solutions and applications in some of the most flexible and adaptable industries such as tourism and hospitality; in order to obtain a more complete picture, the study was oriented in a double perspective, namely the offer from the tourism & hospitality industry, on the one hand and the tourists, on the other hand; regarding the offer from tourism and hospitality, the study used both primary and secondary information, to visualize an image of the existing AI solutions/applications and adopted by the companies in these industries; For the category of tourists, knowing the generational difference regarding the new technologies from the perspective of the level of acceptance and their use, the study aimed at identifying generational profiles regarding the acceptance and use of AI applications in the tourist experience. We consider that the results of the study can be an important support for conducting more complex and comparative studies, related to the use of new technologies that obviously change the development of human society. JEL classification: L86, M15, L83